Non-lactose fermenting Escherichia coli: Following in the footsteps of lactose fermenting E. coli high-risk clones - Mazumder, Razib; Hussain, Arif; Phelan, Jody E.; Campino, Susana; Haider, S. M. Arefeen; Mahmud, Araf; Ahmed, Dilruba; Asadulghani, Md; Clark, Taane G.; Mondal, Dinesh (Frontiers in Microbiology, 2022)
Multi-resistant pathogenic strains of non-lactose fermenting Escherichia coli (NLF E. coli) are responsible for various intestinal and extraintestinal infections. Although several studies have characterised such strains using conventional methods, they have not been comprehensively studied at the genomic level. To address this gap, we used whole-genome sequencing (WGS) coupled with detailed microbiological and biochemical testing to investigate 17 NLF E. coli from a diagnostic centre (icddr,b) in Dhaka, Bangladesh. The prevalence of NLF E. coli was 10%, of which 47% (8/17) exhibited multi-drug resistant (MDR) phenotypes. All isolates (17/17) were confirmed as E. coli and could not ferment lactose sugar. WGS data analysis revealed international high-risk clonal lineages. The most prevalent sequence types (STs) were ST131 (23%), ST1193 (18%), ST12 (18%), ST501 (12%), ST167 (6%), ST73 (6%) and ST12 (6%). Phylogenetic analysis corroborated a striking clonal population amongst the studied NLF E. coli isolates. The predominant phylogroup detected was B2 (65%). The blaCTX-M-15 extended-spectrum beta-lactamase gene was present in 53% of isolates (9/17), whilst 64.7% (11/17) isolates were affiliated with pathogenic pathotypes. All extraintestinal pathogenic E. coli pathotypes demonstrated β-hemolysis. Our study underscores the presence of critical pathogens and MDR clones amongst non-lactose fermenting E. coli. We suggest that non-lactose fermenting E. coli be considered equally capable as lactose fermenting forms in causing intestinal and extraintestinal infections. Further, there is a need to undertake systematic, unbiased monitoring of predominant lineages amongst non-lactose fermenting E. coli that would help in better treatment and prevention strategies.